Hubungan pengetahuan dan sikap ibu tentang stunting dengan pemberian MP-ASI pada anak usia 12-24 bulan - Pratiwi, Rita Dwi; Sari, Diah Ellyana; Darmayanti, Desy; Romlah, Siti Novy (Holistik Jurnal Kesehatan, 2024)
Background: Stunting is a linear growth disorder in children caused by a lack of nutritional intake over a long period of time, characterized by the child's length or height being shorter than his age. Stunting can occur in the womb, where the process of stunting coincides with obstacles to the growth and development of other vital organs. The mother's attitude and knowledge determine parenting patterns that shape behavior in providing MP-ASI to children, which greatly influences the incidence of stunting. Purpose: To analyze the relationship between knowledge and attitudes of mothers about stunting with the provision of complementary foods to children aged 12-24 months. Method: Quantitative research with a descriptive analytical design using primary data (questionnaires) with a cross-sectional approach. The total sample was 50 respondents. The research instrument uses a questionnaire to measure knowledge, attitudes, and provision of MP-ASI which has been tested for validity and reliability. Results: A total of 50 respondents, the majority aged 20-25 years were 22 respondents (44%) with the highest level of education at vocational school level, namely 30 respondents (60%). The level of knowledge of mothers about stunting was mostly in the good category, namely 23 mothers (46.0%). The majority of mothers' attitudes regarding stunting were in the good category, namely 19 mothers (38%) and mothers who were given complementary foods for breast milk were also in the good category, namely 21 mothers (42%). The chi square test on the level of knowledge and attitudes of mothers regarding stunting and giving complementary breast milk shows a p-value of 0.000 or smaller than α=0.05, so there is a relationship between knowledge and attitudes of mothers towards giving complementary breast milk to children. Conclusion: There is a significant relationship between knowledge variables and attitude variables with the provision of complementary foods. Suggestion: It is hoped that it can become material for evaluating community health centers, increase knowledge and insight about stunting and providing complementary foods to children aged 12-24 months, and can become a reference for future researchers.   Keywords: Attitudes; Complementary Food; Knowledge; Stunting.   Pendahuluan: Stunting adalah gangguan pertumbuhan linier pada anak yang disebabkan oleh kurangnya asupan gizi dalam jangka waktu lama, ditandai dengan panjang atau tinggi badan anak lebih pendek dari usianya. Stunting dapat terjadi sejak dalam kandungan, dimana proses terjadinya stunting bersamaan dengan hambatan pertumbuhan dan perkembangan organ-organ vital lainnya. Sikap dan pengetahuan ibu menentukan pola asuh yang membentuk perilaku dalam pemberian MP-ASI pada anak, yang sangat berpengaruh pada kejadian stunting. Tujuan: Untuk menganalisis hubungan pengetahuan dan sikap ibu tentang stunting dengan pemberian MP-ASI pada anak usia 12-24 bulan. Metode: Penelitian kuantitatif dengan desain deskriptif analitik menggunakan data primer (kuesioner) dengan pendekatan cross-sectional. Jumlah sampel sebanyak 50 responden. Instrumen penelitian menggunakan kuesioner untuk mengukur pengetahuan, sikap, pemberian MP-ASI yang telah diuji validitas dan reliabilitasnya. Hasil: Sebanyak 50 responden, mayoritas berusia 20-25 tahun sebanyak 22 responden (44%) dengan tingkat pendidikan terbanyak pada jenjang SMK yaitu 30 responden (60%). Tingkat pengetahuan ibu tentang stunting sebagian besar dalam kategori baik yaitu sebanyak 23 ibu (46.0%). Sikap ibu tentang stunting sebagian besar dalam kategori baik yaitu sebanyak 19 ibu (38%) dan ibu dengan pemberian MP-ASI juga dalam kategori baik berjumlah 21 ibu (42%). Uji chi square terhadap tingkat pengetahuan dan sikap ibu tentang stunting dengan pemberian MP-ASI menunjukkan p-value 0.000 atau lebih kecil dari α=0.05, sehingga terdapat hubungan antara pengetahuan dan sikap ibu terhadap pemberian MP-ASI pada anak. Simpulan: Terdapat hubungan yang signifikan antara variabel pengetahuan dan variabel sikap dengan pemberian MP-ASI. Saran: Diharapkan bisa menjadi bahan evaluasi puskesmas, penambah pengetahuan, dan wawasan tentang stunting dan pemberian MP-ASI pada anak usia 12-24 bulan, serta dapat menjadi acuan bagi peneliti selanjutnya.   Kata Kunci: Pemberian MP-ASI; Pengetahuan; Sikap; Stunting.